A conversation between the sword and the neck: On censorship, colonialism and academic responsibility. - Cardoso, Elsa (Ex Novo: Journal of Archaeology, 2025)
In May 2025, I withdrew a book review and a separate article from al-Masāq: Journal of the Medieval Mediterranean, published by Taylor & Francis, which focuses on cross-cultural dynamics in the premodern Mediterranean world. This decision was not made lightly, and I feel compelled to share the reasons behind it, especially at a time when many of us are grappling with how academia responds (or fails to respond) to the ongoing genocide in Gaza.